PENGARUH PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPEMIND MAPPING TERHADAP HASIL BELAJAR IPS TERPADU - Dwi Isnanto; Maryatun Maryatun (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Education is a long-term investment that requires great effort and funds to improve the quality of Human Resources (HR). One of the ways to improve the quality of human resources is through a good educational process and directed. The purposeof this research is to determine the effect of the use of learning model Co-operative Learning Type Mind Mapping Against Learning Outcomes Integrated Social Studies student grade VIII even semester of SMP Negeri 1 Pekalongan academic year 2017/2018. The subjects in this study were students of class VIII SMP Negeri 1 Pekalongan academic year 2017/2018. This study is an experimental research and aims to determine the difference of learners' learning outcomes from pre-test and post-test that have been given treatment or treatment using cooperative learning model of mind mapping type, also to know the influence of cooperative learning type learning model of mind mapping on learning result of IPS Integrated. The population in this research is class VIII SMP Negeri 1 Pekalongan academic year 2017/2018. The sample of this research is class VIII.1 as experiment class with the number of 30 students and class VIII.2 as control class as many as 29 students. Based on data analysis and hypothesis test using simple linear regression equation obtained a = 24,16, b = 0.76 so that Y '= 24,16 + 0,76X. Form of the instrument in this study can be seen from t arithmetic> t table on significant level 5% that is 5.59> 1.70 and at a significant level of 1% ie 5.59> 2.46Thus the hypothesis is accepted, so it can be said that there is a positive influence the use of cooperative learning type learning model mind mapping on the learning outcomes IPS Integrated students class VIII SMP Negeri 1 Pekalongan academic year 2017/2018.